2018
DOI: 10.1017/s1751731117003639
|View full text |Cite
|
Sign up to set email alerts
|

Effect of condensed tannins in rations of lactating dairy cows on production variables and nitrogen use efficiency

Abstract: The objective of this study was to evaluate the effect of supplemented condensed tannins (CT) from the bark of the Black Wattle tree (Acacia mearnsii) on production variables and N use efficiency in high yielding dairy cows. A feeding trial with 96 lactating German Holstein cows was conducted for a total of 169 days, divided into four periods. The animals were allotted to two groups (control (CON) and experimental (EXP) group) according to milk yield in previous lactation, days in milk (98), number of lactatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 19 publications
4
15
1
Order By: Relevance
“…In the studies of Mokhtarpour et al (2017), Aguerre et al (2016), Ahnert et al (2015), Gerlach et al (2018b) and Perna Junior (2018) the different levels of tannins linearly reduced the urinary N and linearly increased the faecal N. This effect was also observed in this study (Table 7), but there was a reduction of N retention. The change in N excretion from urine to faeces is a widely known tannin effect (Theodoridou et al 2010).…”
Section: Urinary Parameters Microbial Protein and Nitrogen Balancesupporting
confidence: 83%
See 2 more Smart Citations
“…In the studies of Mokhtarpour et al (2017), Aguerre et al (2016), Ahnert et al (2015), Gerlach et al (2018b) and Perna Junior (2018) the different levels of tannins linearly reduced the urinary N and linearly increased the faecal N. This effect was also observed in this study (Table 7), but there was a reduction of N retention. The change in N excretion from urine to faeces is a widely known tannin effect (Theodoridou et al 2010).…”
Section: Urinary Parameters Microbial Protein and Nitrogen Balancesupporting
confidence: 83%
“…The difference may be due to the level of tannins, since these authors included tannins up to 6%. The lack of effect of tannins on micN or EMNS was also observed by Aguerre et al (2016) and Mokhtarpour et al (2017), although they found a reduction on the concentration of rumen ammonia, but Gerlach et al (2018b) found reduction of EMNS. Oliveira et al (2007), using monensin, observed reduction of faecal N. This effect was also observed in the present study, and along with the increased protein digestibility, it may be thought that monensin was important on feed N utilisation.…”
Section: Urinary Parameters Microbial Protein and Nitrogen Balancesupporting
confidence: 62%
See 1 more Smart Citation
“…A feeding trial consisting of four experimental periods was conducted with high-yielding dairy cows. By supplementing a commercial product rich in condensed tannins (CT), an attempt was made to decrease methane emissions and improve the animals’ nitrogen use efficiency, as previously described by [ 34 ]. A total of 96 lactating German Holstein cows (25% primiparous, 112 days in milk (DIM)) were randomly allocated to one of two groups (control (CON) and experimental group (EXP)) and balanced for means of lactation number, DIM, milk yield, and BW.…”
Section: Methodsmentioning
confidence: 99%
“…In dairy cows, CT increased milk quantity but no effects were observed on feed intake. However, various studies described that black wattle tree (Acacia mearnsii) bark containing CT concentration had no effects on dairy cows milk production (Gerlach et al, 2018). Dairy ewes fed quebracho tannins (QT) and acacia species had decreased milk yield.…”
Section: Role Of Tannins On Animal Productionmentioning
confidence: 99%